Overexpression of Human Amyloid precursor protein in Drosophila. - Yagi, Y.; Tomita, S.; Nakamura, M.; Suzuki, T. (Molecular cell biology research communications, 2000)
Amyloid precursor protein (APP) is the precursor of the beta-amyloid peptide which is associated with Alzheimer's disease. The physiological function of APP is not well understood. We have established model system for the analysis of APP function in Drosophila. In neural cells, overexpressed human APP was transported to the synaptic terminal in a manner similar to its localization in human neurons, which suggested that the Drosophila protein transport system localizes human APP appropriately. Expression of APP in imaginal discs resulted in a defect in adult cuticle secretion and a blistered wing phenotype. The severity of the wing blister phenotype was proportional to the APP expression level. These results suggested the presence in Drosophila wing tissue of a protein or protein(s) which can interact with APP.